Consonant changes in the Klaipėda region highlanders dialects: the 21th century situation - Bakšienė, Rima (Lietuvių kalba, 2014)
This paper describes the former Klaipėda region Highlanders area (from Smaliniñkai (Jùrbarkas region) to Juknáičiai (Šilùtė region)) dialectal situation and usage characteristics of consonants in the specific habitat in the beginning of the 21st century. Recent observations suggest that most of consonant changes (hardening of consonants, usage of middle l’, aspirated and slightly voiceless voiced consonants and etc.) described in the previous works of dialectologists captured in the beginning of 21st century. In the old local population language the use cases of hard consonants in the positions of iota softening before suffixes and endings appear quite often. Consonant hardening begins at about Viešvilė surrounding area (Jùrbarkas region) and stronger going westward, mostly hardening cases recorded in the central area of descriptive dialects of Rukai, Pagėgiai, Bitėnai. The most common hardened consonants in the positions of iota softness are r, v, n, example: tràktọrùs ~ traktorius ‘tractor’, keturu∙ ~ keturių ‘of four’; daržõ∙vu. ~ daržovių ‘of vegetables’, lietùvu. ~ lietuvių ‘of Lithuanians’; ˈran.kinu ~ rankiniu ‘manual’, žinuõ∙s ~ žinios ‘news’. A much less often consonants hardening occurs in the root, example: trùš’u. ~ triušių ‘of  rabbits’, gro∙vi∙s ~ griovys ‘ditch’, suntini ~ siuntinį ‘parcel’. In the dialects of the 21st century “middle” l’, common for Klaipėda residents is systematically preserved. In common position of hard l usage in general language this consonant sounds as soft by ear, example: l’a.pαi ~ lapai ‘leafs’, bl’o.gã.i. ~ blogai ‘bad’, kul’dava ~ kuldavo ‘whacked’. In those positions, where in general language it is normal to pronounce the soft l’, example: in iota softening positions this consonant sounds almost as hard l: kõ∙kl’u∙ ~ koklių ‘of  tiles’, kaul’ukùs ~ kauliukus ‘dices’, *š’auluõs ~ Šiauliuose ‘in Šiauliai’. Also other consonant changes occur sometimes in described area: non-motivated softness, aspiration, contraposition neutralization of voiceless and voiced consonants and etc. To be highlighted, as it was earlier as in the presence all described consonant changes are not systematic (are variable) in dialect. Consonant hardening phenomenon is undoubtedly related to the West Lithuanian area of dialects which are characterized by the declination of soft stems.
Keywords: none